Analysis Of The Use Of Fiber-Metal Laminates Material To Reduce Vibrations In L-Extension Type Pedestals Using Finte Element Method - Mochammad Haiqal Bagaskara; Noverdo Saputra (Fakultas Teknik UPN Veteran Jakarta, 2026)
Excessive engine vibration can significantly degrade ship structural durability. This study investigates the application of Fibre-Metal Laminates (FMLs) on an L-extension pedestal to enhance vibration isolation using the impedance mismatch principle. Using Finite Element Analysis (FEA) via Abaqus, various composite inserts (GFRP, CFRP, UD-CFP) and their placement locations were evaluated. The baseline steel pedestal generated a Total Vibration Level Drop of 21.187 dB and a maximum von Mises stress of 28.62 MPa. Modifying the overall structure effectively maximized vibration energy dissipation. Although the 5-layer GFRP yielded the highest damping with 32.013 dB, it triggered extreme local stress 42.65 MPa. Therefore, the 3-layer AL/UD-CFP/AL configuration on the overall structure is the most optimal variation, successfully balancing excellent damping efficiency with 30.098 dB with the safest structural stress limit 33.71 MPa.